SISTEM PEMILIHAN SUARA ONLINE SEDERHANA - Natalis Christian; Ria Karina; Iskandar Itan; Katherine Oktaviani Yap Rui Qi; Celine Te; Grace Vaustine; Jason Hirawan; Putri Utami; Riksen Sitorus; Rina Rina; Saphira Evani; Serly Angelica; She Lee Susanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
This article aims to discuss the performance of the APSON prototype (Aplikasi Pemilihan Suara Online) against the democratic needs of users who need it. The subject of this research is the Student Association of Civil Engineering from Universitas Internasional Batam. The obtained data has derived from various forms of literacy, either physical or online, which has been carefully filtered and reviewed by writers. This research has applied science and technology methods as the method to solve the problem, which also assisted by quantitative data collection techniques, namely documentation techniques, interviews, and online questionnaires. The analysis of this research has given a result as the prototype`s performance is proven to be effective in channeling user`s aspirations without fear of being affected by the risk of COVID-19 pandemic. This decent performance has compiled with various systems, namely the front end(consisting of HTML, Javascript, and CSS) and the back end(consisting of MySQL and PHP). Nevertheless, APSON is still on website-based and in development.